Telecommunications and the city electronic spaces, urban places - Graham, Stephen; Marvin, Simon 1963- (Routledge, 1996)
"debates about technological change and the future of cities. transformation of industrial cities. Dissolving the boundaries between what is 'public' and 'private',' the pervasive applications of telecommunications challenge our accepted notions about the nature of space, time, and distance in the physical world. Telecommunications and the City provides the first critical and state-of-the-art review of the impact of telecommunications on city development and management. Drawing on a range of theoretical approaches and a wide body of research, this book addresses key academic and policy debates about technological change and the future of cities. The complex transformations underway in cities in which telecommunications have central importance are mapped out, and key areas where telecommunications impact the economic, environmental, and institutional development of cities are illustrated." http://www.loc.gov/catdir/enhancements/fy0649/95021880-d.html.
Keywords: Ciudades y pueblos; Stedelijk beleid; Stedelijke ontwikkeling; Telecommunicatie; Télécommunications; Villes, Effets des innovations sur les; Stadt; Cities and towns; Telecommunication; Stadtentwicklung; Telekommunikation; Politische Ökonomie; Aufsatzsammlung